2021
DOI: 10.1073/pnas.2101783118
|View full text |Cite
|
Sign up to set email alerts
|

Spiny and soft-rayed fin domains in acanthomorph fish are established through a BMP-gremlin-shhsignaling network

Abstract: With over 18,000 species, the Acanthomorpha, or spiny-rayed fishes, form the largest and arguably most diverse radiation of vertebrates. One of the key novelties that contributed to their evolutionary success are the spiny rays in their fins that serve as a defense mechanism. We investigated the patterning mechanisms underlying the differentiation of median fin Anlagen into discrete spiny and soft-rayed domains during the ontogeny of the direct-developing cichlid fish Astatotilapia burtoni. Distinct transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 52 publications
(73 reference statements)
0
26
0
Order By: Relevance
“…In some fish, such as sharks and cichlids, it has been shown that FGF signaling is involved in dorsal fin development 19 , 37 . In larval zebrafish, it has also been shown that FGF signaling plays a role in the early stages of LMFF development 10 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In some fish, such as sharks and cichlids, it has been shown that FGF signaling is involved in dorsal fin development 19 , 37 . In larval zebrafish, it has also been shown that FGF signaling plays a role in the early stages of LMFF development 10 .…”
Section: Resultsmentioning
confidence: 99%
“…One influential idea assumes that paired fins arose by co-opting of the genetic patterning modules established during median fin evolution 17 , 52 , 53 . Indeed, gene expression studies in paired and median fins have identified a similar pattern in the expression of developmental genes, such as the nested expression of Hox genes 19 , 37 , 52 54 . We found that prdm16 is expressed in dorsal fin mesenchyme by observations of EGFP expressions in the gt1116A line, and this gene is also expressed in pectoral fin mesenchyme at the early embryonic stage 35 , 55 , 56 .…”
Section: Discussionmentioning
confidence: 99%
“…other cichlids [13,[29][30][31][32][33][34][35]. HDR on the other hand uses a DNA template to guide the repair, thus by providing a single-stranded DNA (ssDNA) template, one can either insert a sequence of interest (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…NHEJ is an imprecise mechanism that generates small insertions or deletions that result in a frameshift. This method has been widely used to induce frameshift mutations in coding protein sequences leading to loss of function alleles in many model systems including other cichlids (Fang et al, 2018;Höch et al, 2021;Kratochwil et al, 2018;Li et al, 2021Li et al, , 2014Livraghi et al, 2021;Rasys et al, 2019;Wang et al, 2021). HDR on the other hand utilises a DNA template to guide the repair, thus by providing a single-stranded DNA (ssDNA) template, one can either insert a sequence of interest (e.g.…”
Section: Introductionmentioning
confidence: 99%